Adjuvant immunotherapy after neoadjuvant immunochemotherapy and esophagectomy for esophageal squamous cell carcinoma: a real-world study - Feng, Jifeng; Wang, Liang; Yang, Xun; Chen, Qixun (Frontiers in Immunology, 2024)
BackgroundThe role of immunotherapy in the adjuvant setting seems promising in recent years. As per the findings of the CheckMate 577 trial, patients with esophageal cancer (EC) who had neoadjuvant chemoradiation with residual pathologic disease should be considered adjuvant immunotherapy (AIT). However, it is unknown if individuals with esophageal squamous cell carcinoma (ESCC) who have received neoadjuvant immunochemotherapy (NICT) followed by radical surgery also require AIT.MethodsA retrospective analysis was performed on the data from patients who underwent NICT and radical surgery for ESCC between 2019 and 2020. To compare disease-free survival (DFS) and overall survival (OS), Kaplan-Meier survival curves were produced. To determine the parameters linked to DFS and OS, a Cox model using hazard ratios (HRs) was completed.ResultsAmong the 292 eligible patients, 215 cases with a mean age of 63.3 ± 6.8 years, including 190 (88.4%) men and 25 (11.6%) women, were finally recruited. The percentage of R0 resection was 98.3%. After NICT, 65 (30.2%) patients achieved pathological complete response. AIT was given to 78 (36.3%) patients following radical resection. For all patients, the 3-year DFS and OS were 62.3% and 74.0%, respectively. In terms of 3-year DFS (61.5% vs. 62.8%, P=0.984) or OS (76.9% vs. 72.3%, P=0.384), no statistically significant difference was found between patients with and without AIT. AIT significantly improved survival in patients with ypT+N+ (DFS: 23.9% vs. 38.5%, P=0.036; OS: 37.0% vs. 61.5%, P=0.010), but not in those with ypT0N0 or ypT+N0. It was found that AIT was related to both DFS (HR: 0.297; P<0.001) and OS (HR: 0.321; P=0.001) in patients with ypT+N+.ConclusionIn ypT+N+ ESCC patients, AIT after NICT followed by radical surgery reduces the recurrence and death, thereby improving the DFS and OS. Randomized controlled trials ought to be conducted to further assess the results of this retrospective investigation.